2019
DOI: 10.21203/rs.2.16805/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal assessment of health-related quality of life among older people with diabetes: results of a nationwide study in New Zealand

Abstract: Background: The current work examined experiences of Health Related Quality of Life (HRQOL) among older adults with a diagnoses of Diabetes Mellitus (DM) over time compared to those without a diagnoses DM. Methods: The sample was drawn from six biennial waves of the New Zealand Health, Work and Retirement survey, a prospective population-based cohort study of older adults 55-70 years at baseline. Data on sociodemographic factors, health behaviours, chronic disease diagnoses and physical and mental HRQOL (SF-12… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Interestingly, in the same study other aspects of QOL, such as self‐esteem and distress associated with being in public, actually improved with age 21 . Furthermore, in a nationwide study from New Zealand on older adults (aged 55‐70 years), obesity was a predictor for poorer QOL, with other predictors including chronic conditions, lower annual income, sight and sleep problems, greater age and fewer years of education 22 . Our own group has also previously reported a correlation between increasing age and worsening physical and sexual functioning in patients with morbid obesity identified for bariatric surgery in our hospital‐based obesity service 23 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, in the same study other aspects of QOL, such as self‐esteem and distress associated with being in public, actually improved with age 21 . Furthermore, in a nationwide study from New Zealand on older adults (aged 55‐70 years), obesity was a predictor for poorer QOL, with other predictors including chronic conditions, lower annual income, sight and sleep problems, greater age and fewer years of education 22 . Our own group has also previously reported a correlation between increasing age and worsening physical and sexual functioning in patients with morbid obesity identified for bariatric surgery in our hospital‐based obesity service 23 .…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, in the same study other aspects of QOL, such as self-esteem and distress associated with being in public, actually improved with age 21. Furthermore, in a nationwide study from New Zealand on older adults (aged 55-70 years), obesity was a predictor for poorer QOL, with other predictors including chronic conditions, lower annual income, sight and sleep problems, greater age and fewer years of education 22.…”
mentioning
confidence: 81%
“…Accordingly, diabetes-related quality of life (D-QOL) concerns the perceptions of the impact of diabetes on health-related quality of life. Many previous studies have demonstrated that diabetes negatively impacts D-QOL because of the lifelong and complex self-management required for this disease (Janssen et al, 2020; Shamshirgaran et al, 2020). Additionally, WD experience worse D-QOL than do men with diabetes (Castellano-Guerrero et al, 2020).…”
mentioning
confidence: 99%